Relational database courses and exercises, ISBN-10 : 3668608482 / ISBN-13 : 978-3668608481 - Kadri Ouahab; Abdelhadi Adel (Grin Verlag, 2017)
This course is intended for computing sophomores and aims at presenting basic principles of relational DBMS and the practice of these fundamentals. The course content is mainly the following: Chapter 1: Introduction to databases Chapter 2: Relational Model Chapter 3: Relational Algebra Chapter 4: Standardization Chapter 5: SQL Language Chapter 6: Practical work A set of exercises are included at the end of the document. We added a tutorial section and directed to allow students to apply the concepts learned in the five chapters.